DEVELOPMENT OF INTERACTIVE CONTENT IN THE EDUCATIONAL PROCESS - Jumayev Turdali Saminjonovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. This article describes the use of modern interactive methods in order to improve the efficiency of the educational process of higher educational institutions. Also, content development and system capabilities are featured on the Quizizz platform, one of the most effective platforms used to stimulate student interest in science and mastery of the subject during class.